(Invited) Mobile Ions, Transport and Redox Processes in Memristive Devices. (19th August 2016) - Valov, Ilia; Luebben, Michael; Wedig, Anja; Waser, Rainer
Abstract : Redox-based resistive switching memories (ReRAM) developed rapidly as most promising candidates for new type non-volatile memory devices fulfilling the demands for green IT i . e . low power consumption, high operation speed and integration density, scalability and reliability. Recent achievements have clearly demonstrated the diversity of applications these devices can be used for – neuromorphics, computing and logic operations, selector elements. All these developments are supported by system functionalities having their origin in the electrochemical nature of the ReRAM cells. In this review the newest achievements in the microscopic understandings of the processes in ReRAMs are discussed. It is shown that both cations and anions (and even noble metal ions) are mobile and can contribute to the resistive switching. The effects of moisture and their importance for both ECM and VCM ReRAMs will be discussed. The influence of different electrode materials in terms of electrocatalytic activity and passivation behavior will be highlighted.